2015
DOI: 10.1016/j.ultsonch.2015.01.009
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ultrasound radiation duration on emulsification and demulsification of paraffin oil and surfactant solution/brine using Hele-shaw models

Abstract: Ultrasound technique is one of the unconventional enhanced oil recovery methods which has been of interest for more than six decades. However, the majority of the oil recovery mechanisms under ultrasound reported in the previous studies are theoretical. Emulsification is one of the mechanisms happening at the interface of oil and water in porous media under ultrasound. Oppositely, ultrasound is one of the techniques using in oil industry for demulsification of oil/water emulsion. Therefore, the conditions in w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 37 publications
0
22
0
Order By: Relevance
“…Also it was noted that energy through these sources may help to have an efficient oil-water de-emulsification process [24] [25] [26]. The aim of these methods is to deliver an external energy into oil through waves.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Also it was noted that energy through these sources may help to have an efficient oil-water de-emulsification process [24] [25] [26]. The aim of these methods is to deliver an external energy into oil through waves.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, ultrasound reduces interfacial tension (IFT) and reservoir oil viscosity, and increases medium temperature, which in turns enhance the displacement efficiency [28,26,29].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Then, one might expect the propagation of ultrasonic waves in the subsurface environment while sending low-frequency elastic waves from the surface (seismic) or due to earthquake nonlinear plane waves (Naderi and Babadagli 2010). A large number of studies have been conducted on the effects of ultrasound on enhanced oil recovery processes, emulsification of oil and brine, oil viscosity, oil mobilization in porous media, phase behaviour of a surfactant-brine-oil system, liquid-liquid interaction, and chemical treatment of horizontal wells (Hamidi et al 2012(Hamidi et al , 2013(Hamidi et al , 2015aBabadagli 2006, 2007;Naderi and Babadagli 2010;Abramov et al 2013Abramov et al , 2015Abramov et al , 2016. All of these studies have shown promising results after applying ultrasonic waves for testing processes.…”
Section: Introductionmentioning
confidence: 99%